(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
This study investigates the diurnal and vertical variations of virtual temperature (Tv) and ambient temperature (T) from 2013 to 2023 in Ilorin. Data analysis reveals that Tv peaks between 1200 and 1400 hours daily, influenced mainly by relative humidity and inversely by temperature changes, with no significant pressure impact. At the planetary boundary layer, Tv and T exhibit marginal differences, converging higher in the troposphere due to diminishing specific humidity. Temporal trends indicate a surface temperature increase of 0.065 degrees and a Tv increase of 0.016 degrees over the past decade. While no simple linear correlation between Tv and relative humidity was found, seasonal patterns suggest potential underlying correlations. This highlights the complex interplay of atmospheric variables in influencing virtual temperature and underscores the need for further investigation into seasonal effects.